Sjoegren syndrome associated with hepatitis C virus: a multicenter analysis of 137 cases (2005)
To define the clinical and immunologic pattern of expression of Sjo¨gren syndrome (SS) associated with chronic hepatitis C virus (HCV) infection, we conducted a multicenter study aiming to collect a large number of patients with SS and HCV infection. Inclusion criteria were the fulfillment of at least 4 of the classification criteria for SS proposed by the European Community Study Group and repeated positive HCV serology, confirmed by recombinant immunoblot assay and/or detection of serum HCVRNA by polymerase chain reaction. One hundred thirty-seven patients were included (104 female and 33 male; mean age, 65 yr). Seventy-nine (58%) patients presented a systemic process with diverse extraglandular manifestations, with articular involvement (44%), vasculitis (20%), and neuropathy (16%) being the most frequent features observed. The main immunologic features were antinuclear antibodies (65%), hypocomplementemia (51%), and cryoglobulinemia (50%). Cryoglobulins were associated with a higher frequency of cutaneous vasculitis, rheumatoid factor, and hypocomplementemia. Thirty-two (23%) patients had positive antiRo/SS-A and/or anti-La/SS-B antibodies; these patients were predominantly women and had a higher prevalence of some extraglandular features and a lower frequency of liver involvement. Nineteen (14%) patients developed neoplasia, with hematologic neoplasia (8 cases) and hepatocellular carcinoma (6 cases) being the most frequent types. Eighty-five percent of SS-HCV patients also fulfilled the recently proposed 2002 classification criteria for SS. In conclusion, HCV-associated SS is indistinguishable in most cases from the primary form using the most recent set of classification criteria. Chronic HCV infection should be considered an exclusion criterion for the classification of primary SS, not because it mimics primary SS, but because the virus may be implicated in the development of SS in a specific subset of patients. We propose the term ‘‘SS secondary to HCV’’ when these patients fulfill the 2002 classification criteria for SS.